Penerapan CSR (Corporate Social Responsibility) PT Sahid Group - Sari Usih Natari; Nurul Mardhiah Sitio (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Implementation of Corporate Environmental Responsibility or CSR (Corporate Social Responsibility) is one of the obligations that must be fulfilled by companies in Indonesia which has been regulated through Article 74 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) as a general implementing regulation. corporate social responsibility/CSR in Indonesia and Government Regulation Number 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies as its implementing regulations.